If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + -7(5x + -8) = 63 + -9x Reorder the terms: 9 + -7(-8 + 5x) = 63 + -9x 9 + (-8 * -7 + 5x * -7) = 63 + -9x 9 + (56 + -35x) = 63 + -9x Combine like terms: 9 + 56 = 65 65 + -35x = 63 + -9x Solving 65 + -35x = 63 + -9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9x' to each side of the equation. 65 + -35x + 9x = 63 + -9x + 9x Combine like terms: -35x + 9x = -26x 65 + -26x = 63 + -9x + 9x Combine like terms: -9x + 9x = 0 65 + -26x = 63 + 0 65 + -26x = 63 Add '-65' to each side of the equation. 65 + -65 + -26x = 63 + -65 Combine like terms: 65 + -65 = 0 0 + -26x = 63 + -65 -26x = 63 + -65 Combine like terms: 63 + -65 = -2 -26x = -2 Divide each side by '-26'. x = 0.07692307692 Simplifying x = 0.07692307692
| 6(x+1)=2(3x+1)+4 | | 11x+5-3x+7= | | x^3+4*x^2+-11*x+30=0 | | 15(a)=225 | | 5x+3=7+5x | | 8(x-3)=-3x-17 | | -7(3x-5)+8=-21x+43 | | 11x-5-3x+7= | | 41=2x+3x+5 | | 3x+20=5x-24 | | 3+-2t=0 | | 4y-4=8x | | 3x-3=3(x-4) | | 3y+4=4+3y | | -5+-1t=0 | | Xy=14forx | | 5(4x+7)=20x+35 | | x^2+8x+74=0 | | f(x)=2(5)2x | | 6a^2+23a-18=0 | | 4y+5=-6+43 | | X-y=45forx | | b^2-8b+63=0 | | 5x-1=2x-70 | | 15=5+10(x-13) | | 5x-8=-7-3x | | 0=16x^2-300x+1000 | | 7x-x+2=15+x | | 16x+4x+2x-3x+x=0 | | X^3+9X+18=0 | | 9x+5x=40 | | -3x^2*2x= |